Hormone receptor status of breast cancers and other prognostic factors in two study centres - Hassan, Mohammad Syauki (2010)
In Malaysia, breast cancer is the commonest cancer in all ethnic. Breast cancer in Malaysian women occurs in the younger age group compared with Western countries and the fourth most common cause of death among all cancers in Malaysia. Stage at presentation here is more advanced with tumor size being much larger and with either locally advanced or metastatic breast cancer. There was a higher proportion of hormone receptor-negative with higher grade tumour in Asian patients compared to Western countries raises questions whether a different pattern of breast cancer is seen in Asian. OBJECTIVES The aim of this study is to evaluate the age at presentation and hormone receptor status of breast cancers and its association with other established prognostic factors for example tumor size, lymph node status and tumour grade. METHODOLOGY This is a study of retrospective record review of 160 patients diagnosed from 1st January 2003 to 31st December 2008. List of name of patients have been obtained from cancer registry of Pathology Department in Hospital University Sains of Malaysia (HUSM) and Hospital Raja Perempuan Zainab II (HRPZ II). The data were obtained from medical xix records. Data were entered into data collection protocol and were analyzed using SPSS software version 12.0. RESULTS This study identifies the association between tumour size and lymph node involvement and staging of breast cancer at presentation. Majority breast cancer patients in this study were from 40 to 49 years old. Minority of patients had tumour size 2cm and below at presentation. The commonest stage at presentation of breast cancer was at stage II and grade III. Only 47.8% were ER (+) and 51.5% were PR (+) respectively. CONCLUSION This study cannot prove of association between young age and receptor status with advanced stage of breast cancer. Majority of patients presented with large size tumour with poorly differentiated histology, estrogen receptor-negative and lymph node metastases.